An All-Arthroscopic, Length-Tensioned Suprapectoral Biceps Tenodesis Technique - Rao, Allison J. (Arthrosc Tech, 2017)
Biceps tenodesis remains a popular choice for treating anterior shoulder pain in the setting of primary biceps tendinitis or biceps pain due to concomitant glenohumeral joint pathology. A variety of surgical approaches and fixation construct options are available for biceps tenodesis. The advantages of an all-arthroscopic biceps tenodesis include anatomic maintenance of the length-tension relation with strength preservation and improved cosmetic results. This technique can be technically challenging but allows for a minimally invasive approach to anchor the biceps. In this Technical Note, we describe a suprapectoral biceps tenodesis using an all-arthroscopic approach in the setting of concomitant rotator cuff repair. This technique offers a viable alternative to the open subpectoral biceps tenodesis.